2002
DOI: 10.1046/j.1365-2044.2002.02624_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Facial fractures and submental tracheal intubation

Abstract: SummarySubmental tracheal intubation is a simple, quick and effective alternative to oral and nasal tracheal intubation or tracheostomy in the surgical management of selected patients with craniomaxillofacial injuries. It has a low morbidity and it does not impede the surgical field, allowing for temporary maxillo-mandibular fixation (jaw wiring) intra-operatively, and nasal assessment, manipulation and bone grafting, either simultaneously or as an independent procedure. We report 12 cases utilizing this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 18 publications
(2 reference statements)
1
77
0
1
Order By: Relevance
“…Reported complications include accidental extubation (17,18), detachment of the pilot balloon (19) or its damage during externalization (20), damage to the cuff of the tracheal tube (15), skin infection (15,21), scar formation (22), tube dislodgement (17), lingual nerve paresthesia, venous bleeding (23), salivary fistula (21,24), and mucocele formation (25). In the present study, minor complications included dislodgement, skin infection, and scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…Reported complications include accidental extubation (17,18), detachment of the pilot balloon (19) or its damage during externalization (20), damage to the cuff of the tracheal tube (15), skin infection (15,21), scar formation (22), tube dislodgement (17), lingual nerve paresthesia, venous bleeding (23), salivary fistula (21,24), and mucocele formation (25). In the present study, minor complications included dislodgement, skin infection, and scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, replacement with oral endotracheal intubation might be proper for prolonged mechanical ventilation, but care is needed as disruption of operation site may occur due to patient's biting of the orotracheal tube [16]. Submandibular approach is a variation from submental approach, and it is well applicable to make a tunnel as the area has better ways around the anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…Extubation after the surgery sometimes is not proceded with the tube remaining, and intermaxillary fixation at this state may cause dangerous situation in airway security due to swelling of tissue. Thus, further studies recommend intermaxillary fixation after the extubation process, and rigid fixation may elimination requirement of intermaxillary fixation [16].…”
Section: Discussionmentioning
confidence: 99%
“…Very low rates of complications have been reported. Many trials have shown the submental route to be simple, quick and safe approach to airway management [1,4,5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Tracheostomy remains an excellent procedure for establishing a formal surgical airway although this procedure may involve a significant risk of iatrogenic complications, such as tracheal stenosis, internal emphysema, damage to laryngeal nerves, tracheoesophagal fistula, and scarring [1,13]. However, this technique involves very meticulous and professional post operative care, and thus prolonged stay in the hospital is required [14].…”
Section: Introductionmentioning
confidence: 99%